Judeo-Spanish on the Web - Rouissi, Soufiane; Štulić, Ana (Infotheca - Journal for Digital Humanities; Vol 15 No 2 (2014): Infotheca - Journal for Digital Humanities, 2024)
The aim of this paper is to give a description of a project involving selection of digital content written in Judeo-Spanish on the Web. By relying on the work done with graduate students, we try to identify pathways of research that would be fruitful for our ongoing work on building a Judeo-Spanish digital collection, which, in turn, can be an important step in saving this endangered language from extinction. The project is carried out through a social bookmarking paradigm, which is a relatively novel way of both individual and collaborative work. Our preliminary observations show that social bookmarking can help us organize our selection of digital content relevant to Judeo-Spanish, as long as the participants are trained to use the social bookmarking tools and if they are sufficiently knowledgeable about the topics of research.